2020
DOI: 10.3390/molecules25061443
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Isotope Effects and Hydrogen Tunnelling in PCET Oxidations of Ascorbate: New Insights into Aqueous Chemistry?

Abstract: Recent experimental studies of kinetic isotope effects (KIE-s) and hydrogen tunnelling comprising three proton-coupled electron transfer (PCET) oxidations of ascorbate monoanion, (a) in aqueous reaction solutions, (b) in the mixed water-organic cosolvent systems, (c) in aqueous solutions of various salts and (d) in fairly diluted aqueous solutions of the various partial hydrophobes are reviewed. A number of new insights into the wealth of the kinetic isotope phenomena in the PCET reactions have been obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…When the Δ G is negative, reduction of the nitroxyl radicals by ascorbate occurs spontaneously, whereas no reduction occurs in the case of a positive Δ G . The involvement of hydrogen tunneling at room temperature was reported based on large kinetic isotope effects (KIE, k H / k D ) in the reduction of TEMPO by ascorbate in water ( k H / k D = 24.2) and water–dioxane mixed solvent (1:1 v/v; k H / k D = 31.0) at room temperature ( 87 , 153 ). A large KIE of 12.8 was also observed for the reaction of ascorbate with 2-phenyl-4,4,5,5-tetramethylimiazolione-1-oxide (PTIO • ) in a phosphate buffer solution at ambient temperatures ( 138 ).…”
Section: Chemistry and Redox Properties Of Nitroxyl Radicalsmentioning
confidence: 99%
“…When the Δ G is negative, reduction of the nitroxyl radicals by ascorbate occurs spontaneously, whereas no reduction occurs in the case of a positive Δ G . The involvement of hydrogen tunneling at room temperature was reported based on large kinetic isotope effects (KIE, k H / k D ) in the reduction of TEMPO by ascorbate in water ( k H / k D = 24.2) and water–dioxane mixed solvent (1:1 v/v; k H / k D = 31.0) at room temperature ( 87 , 153 ). A large KIE of 12.8 was also observed for the reaction of ascorbate with 2-phenyl-4,4,5,5-tetramethylimiazolione-1-oxide (PTIO • ) in a phosphate buffer solution at ambient temperatures ( 138 ).…”
Section: Chemistry and Redox Properties Of Nitroxyl Radicalsmentioning
confidence: 99%
“…Theoretical and empirical research on organohydride donors have established quasi-classical and tunneling contributions to the KIE. From these data, the overall KIE is expected to be dependent on the C–H bond length. In most cases, the quasi-classical contributions remain constant across different combinations of donors and acceptors, but the tunneling contributions to the KIE, and consequently, the total KIE, increase significantly as the C–H bond energy decreases in pure hydride transfer reactions. , However, when the measured KIEs for the reaction between Ru–CO 2+ and BIHs are compared against the hydride transfer reaction free energy changes, which are proportional to the C–H bond hydricity (Δ G H– ), Table , it was observed that as the bond energy decreases, the KIE also decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The isotopic difference, E a (D)– E a (H), (19 kJ mol −1 ) was significantly greater than the difference in zero-point energies of 5.1 kJ mol −1 [ 16 ]. These results indicate that quantum mechanical tunneling plays a role in the hydrogen-transfer reaction from Trolox to DPPH • /β-CD in a phosphate buffer [ 17 , 18 , 19 , 20 ]. ln k H = − E a (H)/( RT ) + ln A H or ln k D = − E a (D)/( RT ) + ln A D …”
Section: Resultsmentioning
confidence: 99%